Nab‐Paclitaxel plus gemcitabine in metastatic pancreatic adenocarcinoma: Australian subset analyses of the phase III MPACT trial. Issue 5 (22nd June 2018) - Young, Rosemary; Mainwaring, Paul; Clingan, Philip; Parnis, Francis Xavier; Asghari, Gholamreza; Beale, Philip; Aly, Abdalla; Botteman, Marc; Romano, Alfredo; Ferrara, Stefano; Margunato‐Debay, Sandra; Harris, Marion
Abstract: Aim: The phase III MPACT trial ( N = 861) demonstrated superior overall survival (OS) with first‐line nab ‐paclitaxel plus gemcitabine versus gemcitabine alone (median, 8.7 months vs 6.6 months; hazard ratio [HR], 0.72; 95% confidence interval [CI], 0.62–0.83; P < 0.001) in patients with metastatic pancreatic cancer. The efficacy benefit of the combination over gemcitabine alone was observed across patient subgroups, including those based on region. This subset analysis was designed to examine the safety and efficacy of nab ‐paclitaxel plus gemcitabine in patients treated in Australia to understand whether differences in patient population or regional variations in patient care had any impact on clinical outcomes. Methods: Patients with metastatic pancreatic cancer received first‐line nab ‐paclitaxel plus gemcitabine or gemcitabine alone in the MPACT study; this analysis focused on those treated in Australia. Results: In the Australian cohort, 120 patients were randomized to receive nab ‐paclitaxel plus gemcitabine ( n = 61) or gemcitabine alone ( n = 59). Median OS was 9.4 months with nab ‐paclitaxel plus gemcitabine versus 6.7 months with gemcitabine alone (HR, 0.64; 95% CI, 0.44–0.94; P = 0.022). Progression‐free survival (median, 5.5 months vs 3.6 months; HR, 0.65; 95% CI, 0.42–1.00; P = 0.049) and the overall response rate (23% vs 2%; P < 0.001) were significantly improved with the combination. No new safety signals were observed. Conclusions: The results of this subset analysis confirm the efficacy and manageable safety profile of nab ‐paclitaxel plus gemcitabine in patients with metastatic pancreatic cancer treated in Australia.